2016
DOI: 10.21037/jgo.2016.11.07
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of tumour-associated B cells and plasma cells in oesophageal and gastric adenocarcinoma

Abstract: These results demonstrate, for the first time, that abundant infiltration of IGKC+ plasma cells independently predicts a prolonged survival in both oesophageal and gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 43 publications
5
43
0
1
Order By: Relevance
“…In 2 of 5 studies, IGKC þ cells were associated with a positive prognostic effect, whereas CD138 þ cells showed no significant association with outcome (12,35). In two other studies, CD138 þ cells showed a positive (35) or negative (38) prognostic effect, whereas IGKC þ cells were neutral. Only 1 of 5 studies found a concordant prognostic effect (positive) for CD138 þ and IGKC þ cells (colorectal cancer; ref.…”
Section: Plasma Cellsmentioning
confidence: 95%
See 4 more Smart Citations
“…In 2 of 5 studies, IGKC þ cells were associated with a positive prognostic effect, whereas CD138 þ cells showed no significant association with outcome (12,35). In two other studies, CD138 þ cells showed a positive (35) or negative (38) prognostic effect, whereas IGKC þ cells were neutral. Only 1 of 5 studies found a concordant prognostic effect (positive) for CD138 þ and IGKC þ cells (colorectal cancer; ref.…”
Section: Plasma Cellsmentioning
confidence: 95%
“…Four studies showed a positive prognostic effect of CD138 þ cells (colorectal cancer, esophageal and gastric cancer, and melanoma; refs. 24,35,43,45), 2 studies found a neutral effect (esophageal cancer and NSCLC; refs. 12,35), and 3 studies showed a negative effect (breast and ovarian cancers, and melanoma; refs.…”
Section: Plasma Cellsmentioning
confidence: 99%
See 3 more Smart Citations